2011
DOI: 10.1093/bja/aer061
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of transversus abdominis plane block vs spinal morphine for pain relief after Caesarean section

Abstract: Spinal morphine-but not TAP block-improved analgesia after Caesarean section. The addition of TAP block with bupivacaine 2 mg kg(-1) to spinal morphine did not further improve analgesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
171
2
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(180 citation statements)
references
References 24 publications
(15 reference statements)
3
171
2
4
Order By: Relevance
“…4 Other studies confirmed the effectiveness after Caesarean section with lower pain scores, less opioid requirement and thereby fewer side effects. 11,[13][14][15] Even though the effect of TAP block as multimodal analgesia has been confirmed in different randomised clinical trials, 11,[13][14][15][16][17] whether posterior and lateral approach TAP block have differences in efficacy and duration of analgesic effect has remained controversial. However, in one meta-analysis study, the posterior TAP block technique appeared to have more prolonged analgesia effect than the lateral TAP block in lower abdominal significant (nausea 5.8% vs. 1.9%, p = 0.45 and vomiting 7.7% vs. 0%, p = 0.06) (see Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…4 Other studies confirmed the effectiveness after Caesarean section with lower pain scores, less opioid requirement and thereby fewer side effects. 11,[13][14][15] Even though the effect of TAP block as multimodal analgesia has been confirmed in different randomised clinical trials, 11,[13][14][15][16][17] whether posterior and lateral approach TAP block have differences in efficacy and duration of analgesic effect has remained controversial. However, in one meta-analysis study, the posterior TAP block technique appeared to have more prolonged analgesia effect than the lateral TAP block in lower abdominal significant (nausea 5.8% vs. 1.9%, p = 0.45 and vomiting 7.7% vs. 0%, p = 0.06) (see Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…All the studies reported the 24-hr pain score, and 11 trials documented the 24-hr morphine consumption. 22,24,27,29,34,35,44,46,47,56,57 Transversus abdominal plane block did not significantly reduce the pain score (Table 2) at 24 hr but significantly reduced the mean 24-hr opioid consumption by 10 mg (95% CI, -17.4 to -2.8; P = 0.006) compared with the control group ( Table 2). The US-guided and landmark subgroup analyses for Cesarean delivery studies are presented in Table 3.…”
Section: Transversus Abdominal Plane Block Vs Local Infiltrationmentioning
confidence: 95%
“…[44][45][46][47] Use of ITM also reduced VAS score by 0.7 (95% CI, 0.3 to 1.1; P = 0.001) at six hours. Only one trial 45 evaluated the 12-hr pain score.…”
Section: Transversus Abdominal Plane Block Vs Intrathecal Morphinementioning
confidence: 96%
“…The type of analgesia provided by NSAIDs has been shown to be directed against the visceral cramping pain occurring after Cesarean delivery; 20,21 however, all three patients complained of predominantly somatic incisional pain (as opposed to visceral pain) for which TAP blocks are particularly indicated. [8][9][10] The analgesic efficacy of TAP blocks for these three women indicates that the pain was likely predominantly somatic incisional pain. Differentiation between incisional and cramping pain is important before offering TAP blocks as a rescue analgesic technique, as visceral pain from the uterus will not be adequately treated with TAP blocks.…”
Section: Discussionmentioning
confidence: 92%
“…6,7 Additionally, studies show that intrathecal morphine provides better post-Cesarean delivery analgesia compared with TAP blocks. 6,[8][9][10] The role of TAP block for rescue analgesia following surgery is not well described and poorly studied. Borglum et al describe a four-point TAP block technique as a rescue procedure in 25 patients who had undergone abdominal surgery other than Cesarean delivery under general anesthesia.…”
Section: Résumémentioning
confidence: 99%